2019
DOI: 10.1186/s12889-019-7716-y
|View full text |Cite
|
Sign up to set email alerts
|

Supervised training in primary care units but not self-directed physical activity lowered cardiovascular risk in Brazilian low-income patients: a controlled trial

Abstract: BackgroundPublic health strategies to increase physical activity in low-income communities may reduce cardiovascular risk in these populations. This controlled trial compared the cardiovascular risk estimated by the Framingham Risk Score (FRS) over 12 months in formally active (FA), declared active (DA), and physically inactive (PI) patients attended by the ‘Family Health Strategy’ in low-income communities at Rio de Janeiro City, Brazil (known as ‘favelas’).MethodsPatients were matched for age and assigned in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although Brazil has a large program that includes PA professionals in primary health care (Multidisciplinary Primary Care Teams), the distribution of the units with PA interventions is unequal considering different geographical regions [ 26 ]. The supervised PA promoted by the different programs already proved to be effective, even in highly deprived areas, such as in “ favelas ” [ 14 , 27 ]. Also, both the building of public PA facilities and the stimulation of community health programs for the stimulation of PA should be taken together.…”
Section: Discussionmentioning
confidence: 99%
“…Although Brazil has a large program that includes PA professionals in primary health care (Multidisciplinary Primary Care Teams), the distribution of the units with PA interventions is unequal considering different geographical regions [ 26 ]. The supervised PA promoted by the different programs already proved to be effective, even in highly deprived areas, such as in “ favelas ” [ 14 , 27 ]. Also, both the building of public PA facilities and the stimulation of community health programs for the stimulation of PA should be taken together.…”
Section: Discussionmentioning
confidence: 99%
“…This situation requires alternative approaches, such as for example, walking meetings, which has been reported to also lead to social benefits ( 161 ), as well as some recently proposed solutions with promising results, including intermittent upper body ergometry, an attractive option for those who prefer to remain in the seated position ( 162 ), and low-cost standing desks, which are made out of cardboard, are suitable for use in different locations such as at home, and can have an inexpensive and environment-friendly recycling process ( 163 , 164 ). Despite the challenges involved in implementing public policies that contemplate widespread access to PA promotion and sedentary behavior reduction initiatives, especially in low-income settings, localized comprehensive interventions have been recently implemented in many countries, including Canada and Brazil, and must be scaled up ( 60 , 101 , 146 , 165 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that modifying one's routine to include PA was shown to be impractical due to different reasons, such as tiresome jobs, long commutes, holding more than one job and/or also studying, and competing housework chores and/or family responsibilities ( 47 , 99 ). Although different barriers to PA are found in specific regions ( 95 , 100 ), low income is associated with PA insecurity in high- as well as lower-income countries ( 47 , 101 ).…”
Section: Macro-environmental Dimensions Of Physical Activitymentioning
confidence: 99%
“…One recent study aimed to improve the prevention care capacity of the FHS teams by integrating a supervised physical activity program found reductions in cardiovascular risk among adults that live in lowincome communities in Rio de Janeiro City. 84 Another study from the Federal District found that the promotion of healthy eating habits and physical exercise by the FHS teams was associated with reductions in risk factors in overweight among adults. 85 Prioritizing disease prevention is also paramount in Turkey in order to address the rapid rise chronic diseases and modifiable risk factors such as rapidly rising obesity, particularly among women, and persistently high prevalence of smoking.…”
Section: Discussionmentioning
confidence: 99%